Reduced proliferation of bone marrow MSC after allogeneic stem cell transplantation is associated with clinical outcome - Katzerke, Christiane; Schaffrath, Judith; Lützkendorf, Jana; Janssen, Maike; Merbach, Anne Kathrin; Nerger, Katrin; Binder, Mascha; Baum, Cornelia; Lauer, Kirstin; Rohde, Christian; Willscher, Edith; Müller-Tidow, Carsten; et al. (Blood advances, 2023)
Engraftment and differentiation of donor hematopoietic stem cells is decisive for the clinical success of allogeneic stem cell transplantation (alloSCT) and depends on the recipient’s bone marrow (BM) niche. A damaged niche contributes to poor graft function after alloSCT; however, the underlying mechanisms and the role of BM multipotent mesenchymal stromal cells (MSC) are ill-defined. Upon multivariate analysis in 732 individuals, we observed a reduced presence of proliferation-capable MSC in BM aspirates from patients (N = 196) who had undergone alloSCT. This was confirmed by paired analysis in 30 patients showing a higher frequency of samples with a lack of MSC presence post-alloSCT compared with pre-alloSCT. This reduced MSC presence was associated with reduced survival of patients after alloSCT and specifically with impaired graft function. Post-alloSCT MSC showed diminished in vitro proliferation along with a transcriptional antiproliferative signature, upregulation of epithelial-mesenchymal transition and extracellular matrix pathways, and altered impact on cytokine release upon contact with hematopoietic cells. To avoid in vitro culture bias, we isolated the CD146+/CD45-/HLA-DR- BM cell fraction, which comprised the entire MSC population. The post-alloSCT isolated native CD146+MSC showed a similar reduction in proliferation capacity and shared the same antiproliferative transcriptomic signature as for post-alloSCT colony-forming unit fibroblast-derived MSC. Taken together, our data show that alloSCT confers damage to the proliferative capacity of native MSC, which is associated with reduced patient survival after alloSCT and impaired engraftment of allogeneic hematopoiesis. These data represent the basis to elucidate mechanisms of BM niche reconstitution after alloSCT and its therapeutic manipulation.
Im Voraus online veröffentlicht in "Blood Advances First Edition": 10. Februar 2023, Artikelversion: 16. Juni 2023
Gesehen am 01.08.2023